Effect of growth temperature on the structural and optical properties of CdS:O thin films for CdTe solar cells - Das N.K.; Chakrabartty J.; Farhad S.F.U.; Matin M.A.; Amin N. (Institute of Electrical and Electronics Engineers Inc., 2023)
Cadmium sulfide; Cadmium sulfide solar cells; Cadmium telluride; Energy gap; Growth temperature; II-VI semiconductors; Image enhancement; Light transmission; Lime; Optical properties; Sulfur compounds; Thin film solar cells; Ultraviolet visible spectroscopy; CdTe solar cells; Radio-frequency sputtering; Soda-lime glass; Structural and optical properties; Substrate temperature; Transmission spectrums; UV-vis spectroscopy; Visible wavelengths; Thin films